A gestão do poder judiciário uma análise do sistema de mensuração de desempenho do judiciário brasileiro - Nogueira, José Marcelo Maia (2010)
This research presents an analysis of the Brazilian judiciary performance measurement system, specifically with regard to the process of dissemination and usage of the act of measuring in the organizational culture of the judiciary units across the country. After literature and documentary review, the experience of European judiciary in measuring performance is taken as a comparative reference to the Brazilian system. The managers' perceptions of the system in respect of their understanding about the performance management and measurement in the judiciary are also considered, as well as of the political efforts and administrative models adopted, and the future possibilities of the system. Since this work access a first time experience of the adoption of performance measurement as a national policy, the study also discusses the kind of structural and organizational challenges, faced by the Brazilian judiciary, that will need to be dealed with, in order to solidify the measurement process besides the eventual need for standardization in administrative proceedings due to the heterogenity of the Brazilian judicial organizations.